Black Languaging IS Translanguaging: We Not Just Talkin Bout It, We Bout It Bout It! - Privette, Chelsea; Saechao, Karina R. (Perspectives of the ASHA Special Interest Groups, 2025)
Purpose: The purpose of this article is to provide a foundational understanding of translanguaging in order to conceptualize Black Languaging as translanguaging and to expand our definition of multilingualism and reframe how we think about Black Language in schools. Method: The authors summarize seminal literature in translanguaging and racio-linguistic ideologies in order to theorize about Black Language within a trans-languaging framework. Results: Centering Black Languaging within a translanguaging framework further implicates the sociopolitical ideologies that shape our conceptualizations of language and dialect and the educational experiences of racially and linguistically minoritized students. Conclusion: A sociopolitically informed definition of Black Language allows us to blur the boundaries of languages and dialects and think of all students--especially racially minoritized students--as translanguaging in co-community.